PENERAPAN STRATEGI PEMBELAJARAN ANALOGI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID KELAS XI IPA SMA NEGERI 3 PEKANBARU - Kurniaty Utami; Maria Erna; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Research on the application of analogy learning strategy has been applied to improve student learning achievement on the topic of colloid class XI Science of Senior High School Number 3 Pekanbaru on May 2016. The research is experimental research based on pretest-posttest design. The samples consisted student of two classes, XI Science 3 as experimental class and XI Science 2 as control class that randomly selected after testing normality and homogeneity. Analogy Learning Strategy applied in XI Science 3. Analysis of data used t-test. Results of data processing obtained tcount> ttable (4,84>1,67). It means that the application of analogy learning strategy can improve student learning achievement on the topic of colloid in class XI Science of Senior High School Number 3 Pekanbaru. The improvement category of student learning achievement at experimental class was high category with normalized N gain which 0, 71.Keywords : Analogy Learning Strategy, Learning Achievement and Colloid.